2019
DOI: 10.1002/pon.5291
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Smoking‐Related Causal Attributions and Risk Perceptions in Cervical Cancer Survivors

Abstract: Objective The prevalence of smoking among cervical cancer survivors typically exceeds what is found among women in the general population and other cancer survivors. Yet, there is a dearth of literature on risk and protective factors related to smoking among cervical cancer survivors, especially when it comes to identification of variables that are amendable to intervention. To help fill this gap in the literature, this qualitative study examines the nature of smoking‐related causal attributions and risk perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The results indicate that some potential obstacles to overcome are low motivation to quit and pessimistic beliefs about one’s ability to do so successfully. Other studies have found CCS and those with cervical dysplasia do not understand or appreciate fully the potential causal link between smoking and their (pre)cancerous condition or the risks of continued smoking on their future health (Costanzo et al, 2005; Hoover et al, 2019; Puleo et al, 2020). In addition, there is evidence rural cancer survivors have lower levels of health literacy than their nonrural counterparts (McDougall et al, 2018), which might be a factor here given the high number of rural-dwelling CCS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results indicate that some potential obstacles to overcome are low motivation to quit and pessimistic beliefs about one’s ability to do so successfully. Other studies have found CCS and those with cervical dysplasia do not understand or appreciate fully the potential causal link between smoking and their (pre)cancerous condition or the risks of continued smoking on their future health (Costanzo et al, 2005; Hoover et al, 2019; Puleo et al, 2020). In addition, there is evidence rural cancer survivors have lower levels of health literacy than their nonrural counterparts (McDougall et al, 2018), which might be a factor here given the high number of rural-dwelling CCS.…”
Section: Discussionmentioning
confidence: 95%
“…The methods of this embedded mixed-methods study, including the eligibility criteria, recruitment strategy, and enrollment procedures are described in detail elsewhere (Puleo et al, 2020) and are only summarized here. Briefly, the quantitative aspect of the study allowed comprehensive measurement of key behavioral variables that have yet to be fully described in the literature (e.g., cigarettes per day, quit attempts) while the qualitative aspect of the study involved open-ended questions meant to uncover what variables CCS believe contribute to smoking and undermine quitting.…”
Section: Methods Design and Participantsmentioning
confidence: 99%
“…The timing of referral to a smoking cessation service could be more effective at a time-point other than the initial consultation. The highest quit attempts occur within the 12-months post-diagnosis and rates continued but decline after diagnosis according to an Australian study of 3315 mixed cancer-type patients 30 . The eMR flagging system allowed HCPs to re-assess cessation, which is considered an important step given that a patient's motivation to quit can be prolonged 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Topics of these scholarly articles include a range of topics that illustrate the diversity of experiences occurring through the program. Publication topics include the relationship between body composition and immunity (Al-Attar et al, 2018), prostate cancer biology Hensley et al, 2019), colorectal cancer biology (Gan et al, 2020;Stevens et al, 2018;Xiong et al, 2020), nutritional programs (Weber et al, 2021), health insurance literacy in colorectal cancer survivors (Edward et al, 2021), smoking-related cervical cancer (Borger et al, 2021;Puleo et al, 2020), novel xenograft methods (Haney et al, 2020), neuroendocrine tumors (Chow et al, 2021), and T Cell biology (Presnell et al, 2020).…”
Section: Career Support and Post-participation Mentoringmentioning
confidence: 99%